2021
DOI: 10.1111/josi.12446
|View full text |Cite
|
Sign up to set email alerts
|

Legal socialization during adolescence: The emerging role of school resource officers

Abstract: Adolescence and later childhood are critical periods for developing attitudes toward legal authorities, a process known as legal socialization. Traditionally, scholars have understood contact with local police officers and experiences with the juvenile justice system to drive legal socialization. These interactions, and in particular how fair they are perceived to be, influence long-term views about the legitimacy of the legal system and future criminal behavior. In recent years, however, the potential for ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Ideally, perceptions of police legitimacy should also be measured at age 13 in order to estimate the strength of the direct "generalized" pathway against the indirect pathways. In addition, the current study only focused on the connection between teacher and police authorities, whereas previous research has shown that relationships with parents, peers, and other authorities during adolescence may be associated with attitudes towards the police (e.g., Cavanaugh & Cauffman, 2015;Granot et al, 2021;Kaiser & Reisig, 2017). Future research should examine whether and to what extent these experiences generalize to one another, and how do these effects play out over the life course.…”
Section: Discussionmentioning
confidence: 96%
“…Ideally, perceptions of police legitimacy should also be measured at age 13 in order to estimate the strength of the direct "generalized" pathway against the indirect pathways. In addition, the current study only focused on the connection between teacher and police authorities, whereas previous research has shown that relationships with parents, peers, and other authorities during adolescence may be associated with attitudes towards the police (e.g., Cavanaugh & Cauffman, 2015;Granot et al, 2021;Kaiser & Reisig, 2017). Future research should examine whether and to what extent these experiences generalize to one another, and how do these effects play out over the life course.…”
Section: Discussionmentioning
confidence: 96%
“…Research has not yet evaluated whether SROs influence longer term perceptions of police in general. As previous research suggests (Granot et al, 2021), SROs may serve as a key aspect of the legal socialization process as one of the earlier contacts youth have with the justice system. However, research thus far has only evaluated whether SROs affect perceptions of police outside of school at that same age.…”
Section: Do Sros Influence Police Perceptions?mentioning
confidence: 96%
“…Jackson (2002) examined a sample of 271 students from schools in Missouri and found that there was no relationship between the use of SROs and perceptions of police in general. Granot et al (2021) administered a survey to high-school students in the northeastern region of the United States to evaluate whether adolescent perceptions of SROs are related to their perceptions of law enforcement in the community. The findings revealed that perceptions of SROs were associated with the perceived legitimacy and willingness to comply with police in general.…”
Section: Do Sros Influence Police Perceptions?mentioning
confidence: 99%
See 2 more Smart Citations